Hydroxypropyl-β-Cyclodextrin Functionalized Graphene Oxide Nanospheres as Unmodified Paclitaxel Carriers - He, Yi; Chen, Danfeng; Xiao, Guomin (Asian Journal of Chemistry, 2014)
This work reports a novel type of electrosprayed graphene oxide nanospheres consisting of gelatin and hydroxypropyl-b-cyclodextrin functionalized graphene oxide sheets to support water insoluble anticancer drug paclitaxel. The drug loading content and drug loading efficiency were as high as 14.9 μg/mg and 59.5 %, respectively. The slow and smooth in-vitro release profiles of paclitaxel were assigned to the strong interaction between graphene oxide sheets and the hydroxypropyl-b-cyclodextrin molecules, in addition to the encapsulation of electrosprayed graphene oxide nanospheres.